Yield and its attributes as affected by planting dates in soybean (Glycine max) varieties - BHATIA, V S; TIWARI, S P; JOSHI, O P (The Indian Journal of Agricultural Sciences, 2013)
A field study was conducted for 2 years during 1992-93 to find out the genotypic response in terms of yield and its attributes and to assess the suitability of varieties under varying planting dates. The experiment comprised of 5 planting dates and 12 predominant soybean (Glycine max (L.) Merr.) varieties. Significant differences were obtained for yield and most of the yield attributes among planting dates and among varieties. Early planting by 20 June was found to be the most appropriate for high seed yield (I 666 kg/ha) across years and varieties. In subsequent plantings of 30 June; 10,20 and 30 July, there were yield reduction of 4.8,8.5,28.1 and 39.7% respectively. Suitable soybean varieties, viz ’JS 335’, ’NRC 2’ and ’JS 71-05’ were identified to give high soybean yield across all planting dates and years. The reduction in seed yield due to late plantings was mainly due to the combined effect of reduced total biomas, pods/plants, plant height, number of branches, 100 seed weight, days to flowering and days to maturity.